Purification and Reconstitution of an Integral Membrane Protein, the Photoreaction Center of Rhodobacter sphaeroides, Using Synthetic Sugar Esters. (June 2000) - Peters, H.; Schmidt-Dannert, C.; Cao, L.; Bornscheuer, U.T.; Schmid, R.D.
Detergents are indispensable reagents for the extraction and solubilization of integral membrane proteins, but their removal from a reconstituted phospholipid-protein complex is usually desirable. In this paper, we describe a novel method in which the synthetic sugar esters 6-O-octanoyl-β-Dglucose (OG) or 6-O-octanoyl-β-D-mannose (OM) are used as detergents for both the isolation and the rapid reconstitution of the photosynthetic reaction center protein of Rhodobacter sphaeroides . Following solubilization of the reaction center with OG or OM and reconstitution of this protein in liposomes, a convenient removal of these detergents was achieved within less than two hours by hydrolytic cleavage of the sugar esters using immobilized lipases. Best results were achieved with lipase from Bacillus sp. immobilized on silica gel.